Energy Technology 2012 : Ccarbon Dioxide Management and Other Technologies ; Proceedings of Symposia Sponsored by the Energy Committee of the Extraction and Processing Division and the Light Metals Division of TMS (The Minerals, Metals & Materials Society), Held during the TMS 2012 Annual Meeting & Exhibition, Orlando, Florida, USA, March 11-15, 2012 - Salazar-Villalpando, Maria D. (Wiley, 2012)
Proceedings of symposia sponsored by the Energy Committee of the Extraction and Processing Division and the Light Metals Division of TMS (The Minerals, Metals & Materials Society)Held during the TMS 2012 Annual Meeting & Exhibition Orlando, Florida, USA, March 11-15,2012.